181k views
2 votes
Simplify expression

Simplify expression-example-1

1 Answer

2 votes

\bf ~~~~~~~~~~~~\textit{negative exponents}\\\\ a^(-n) \implies \cfrac{1}{a^n} \qquad \qquad \cfrac{1}{a^n}\implies a^(-n) \qquad \qquad a^n\implies \cfrac{1}{a^(-n)} \\\\ -------------------------------


\bf \cfrac{6cd^4* -2d^5}{c^3(6d^4)^2}\implies \cfrac{(6\cdot -2)cd^4d^5}{c^3(6^2d^(4\cdot 2))}\implies \cfrac{-12cd^4d^5}{c^336d^8} \\\\\\ \cfrac{-12}{36}\cdot \cfrac{cd^4d^5}{c^3d^8}\implies -\cfrac{1}{3}\cdot \cfrac{d^4d^5d^(-8)}{c^3c^(-1)}\implies \cfrac{1}{3}\cdot \cfrac{d^(4+5-8)}{c^(3-1)}\implies \cfrac{d}{3c^2}
User Mahedi Sabuj
by
5.7k points